Hemodynamic Instability during Dialysis: The Potential Role of Intradialytic Exercise - McGuire, Scott (Biomed Res Int, 2018)
Acute haemodynamic instability is a natural consequence of disordered cardiovascular physiology during haemodialysis (HD). Prevalence of intradialytic hypotension (IDH) can be as high as 20–30%, contributing to subclinical, transient myocardial ischemia. In the long term, this results in progressive, maladaptive cardiac remodeling and impairment of left ventricular function. This is thought to be a major contributor to increased cardiovascular mortality in end stage renal disease (ESRD). Medical strategies to acutely attenuate haemodynamic instability during HD are suboptimal. Whilst a programme of intradialytic exercise training appears to facilitate numerous chronic adaptations, little is known of the acute physiological response to this type of exercise. In particular, the potential for intradialytic exercise to acutely stabilise cardiovascular hemodynamics, thus preventing IDH and myocardial ischemia, has not been explored. This narrative review aims to summarise the characteristics and causes of acute haemodynamic instability during HD, with an overview of current medical therapies to treat IDH. Moreover, we discuss the acute physiological response to intradialytic exercise with a view to determining the potential for this nonmedical intervention to stabilise cardiovascular haemodynamics during HD, improve coronary perfusion, and reduce cardiovascular morbidity and mortality in ESRD.